Produktivitas Primer Rawa Jombor, Klaten, Jawa Tengah - Anggraeni, Belinda Dian; Jati, Wibowo Nugroho; Zahida, Felicia (Universitas Atma Jaya Yogyakarta, 2003)
Primary productivity of Jombor Swamp, Klaten has been assessed in order to understand its water quality. The method used was using light-dark bottles incubated for 4 hours. Samples were taken between 6-10, 10-14 and 14-18 hour, under the depth 0.2, 1.5, and 3 m. The results showed that productivity in April – 2.4 to 2.17 ppm, May –0.6 to 2 ppm, and June –2.1 to 3.4 ppm. The regression correlation of the productivity to phytoplankton`s density is y = -0.03 + 0.01 x and r = 0.76, productivity to light intensity is y = -5.04 + 0.01 x and r = 0.63, productivity to water depth is y = 0.56 + 0.12x and r = 0.31, productivity to turbidity is y = 1,78 + 0.33x and r = 0.35, productivity to water temperature is y = 1.91 – 0.08x and r = 0.32, productivity to pH is y = 1.39 – 0.71x and r = 0.20, and productivity to CO2 content is y = 1.77 – 0.11 and r = 0.29. Based on the overall findings, the water quality condition was classified as eutrophic.